PERAN KECERDASAN INVESTOR DALAM PENILAIAN PASAR TERHADAP MANAJEMEN LABA - Ryani Hanna Pertiwi, Deni Darmawati (Media Riset Akuntansi, Auditing & Informasi, 2011)
The purpose of this study is to investigate the role of investor sophistication in market valuation to earnings management. The sample of the study was the manufacturing companies listed in the Indonesia Stock Exchange. The data was collected using purposive sampling method. The number of the company was 57. The result of this study shows that: (1) earnings management has significantly positive influence to cummulative abnormal return (2) interaction variable between investor sophistication with earnings management has significantly negative influence to cummulative abnormal return, it means that the investor sophistication could reduce the error in market of valuation to analyze financial information.